(untitled) (REMUNOM, 2025)
This study aims to identify how the distance learning training course for authorized civil servants, "Assistance to People with Disabilities in Public Spaces," offered by the Judicial School, can contribute to the inclusion of people with disabilities in the work context of the TJPE. This training initiative aimed to assess the impact of the course on the daily work of the civil servants who participated, in order to support the implementation of more effective inclusion policies within the judiciary. Twenty-six participants completed the questionnaires. Behavioral changes were observed, such as the way people look at people in wheelchairs and the way they interact with deaf people, where they began to understand that they should look at them, not interpret. Other actions were also cited, such as increased sensitivity toward diversity and an interest in deepening their knowledge of accessibility-related topics. At the end of the investigation, it was possible to identify, in the context of staff training, which educational strategies proved most effective in promoting truly accessible and inclusive service at the TJPE.